Comparison Effects Of Seaweed Concentrations On Total Bacteria And Yeast Kombucha Gracilaria Verrucosa During The Production Process. Issue 1 (1st July 2022) - Andrianto, Wahyu; Sudarno,; kusdarwati, Rahayu; nirmala, dan Dwitha
Abstract: Yeasts and bacteria used in the fermentation of kombucha Gracilariaverrucosa require nutrients to be able to grow and function optimally. The carbohydrate content of seaweed Gracilaria verrucosa is one of the factors that affect the growth of bacteria and yeasts that play a role in producing kombucha beverage products. The purpose of this study was to determine the effect of comparison of seaweed concentrations on total bacteria and yeast kombucha seaweed during the production process. The method used in this study is an experimental method with a completely randomized design (CRD) with six treatments and 4 replications. The result of this research is that the concentration of seaweed affects the total total bacteria and yeast during the kombucha production process. Tests on the total bacteria showed that the total number of bacteria treated by P0 increased up to day 3 with the highest total bacteria at 1.7x107 CFU/ml. On the 3rd day total yeast also increased, the highest yield of total yeast in treatment P1 was 1.9x107 CFU/ml.